A systematic review and meta-analysis of retrograde type A aortic dissection after thoracic endovascular aortic repair in patients with type B aortic dissection. Issue 15 (14th April 2023) - Ali-Hasan-Al-Saegh, Sadeq; Halloum, Nancy; Scali, Salvatore; Kriege, Marc; Abualia, Mohannad; Stamenovic, Davor; Bashar Izzat, Mohammad; Bohan, Patrick; Kloeckner, Roman; Oezkur, Mehmet; Dorweiler, Bernhard; Treede, Hendrik; et al.
Abstract : Background: Retrograde type A dissection (RTAD) is a devastating complication of thoracic endovascular repair (TEVAR) with low incidence but high mortality. The objective of this study is to report the incidence, mortality, potential risk factors, clinical manifestation and diagnostic modalities, and medical and surgical treatments. Methods: A systematic review and single-arm and two-arm meta-analyses evaluated all published reports of RTAD post-TEVAR through January 2021. All study types were included, except study protocols and animal studies, without time restrictions. Outcomes of interest were procedural data (implanted stent-grafts type, and proximal stent-graft oversizing), the incidence of RTAD, associated mortality rate, clinical manifestations, diagnostic workouts and therapeutic management. Results: RTAD occurred in 285 out of 10, 600 patients: an estimated RTAD incidence of 2.3% (95% CI: 1.9–2.8); incidence of early RTAD was approximately 1.8 times higher than late. Wilcoxon signed-rank testing showed that the proportion of RTAD patients with acute type B aortic dissection (TBAD) was significantly higher than those with chronic TBAD ( P = .008). Pooled meta-analysis showed that the incidence of RTAD with proximal bare stent TEVAR was 2.1-fold higher than with non-bare stents: risk ratio was 1.55 (95% CI: 0.87–2.75; P = .13). Single arm meta-analysis estimated a mortality rate of 42.2% (95% CI: 32.5–51.8), with an I 2 heterogeneity of 70.11% ( P < .001). Conclusion: RTAD is rare after TEVAR but with high mortality, especially in the first month post-TEVAR with acute TBAD patients at greater risk as well as those treated with proximal bare stent endografts.